The Practice of Using and/or Cutting The Body With Sharp Objects: A Case Study of University Students’ Risk Awareness in Selected Universities in Abia State - E.E.Enwereji; E I. Akubugwo; J.O.Onwuka; D.C.Chikezie (Journal of Clinical Research In HIV AIDS And Prevention, 2018)
Introduction The practices of having extreme and permanent body modifications as in tattoos and scarifications are gaining popularity among youths especially those in the universities. Not minding the unbearable and painful pressure of sharp objects on the tissues and the risk of being infected with blood transmitted infections including HIV, youths still engage in these practices. This study aimed to examine the extent to which university students are aware of the risks of using improperly sterilized and disinfected sharp objects. Materials and Method First year students in three universities, Federal, State and Private Universities were used for the study. A random sample of ninety (90) students made up of 30 students from each of the three universities studied was used. Drama was used as an intervention that will create awareness on risks of utilizing sharp objects in making scarifications. The completed copies of self-administered pre- and post-drama questionnaire were collected and analyzed quantitatively using Tables and percentages. Results Results showed that a good number of students 29 (97%) in Michael Okpara University of Agriculture (MOUA) , 28(93%) in Abia State University (ABSU) and 27( 90%) in Rhema University viewed sharing sharp objects like razor blades and syringes as risk to blood transmitted infections especially HIV. A total of 28(31%) of students both males and females in MOUA, ABSU, and Rhema had marks (scarification and/ or tattoos) on the body. The main reason for having the marks was for traditional identification and this was more among students in MOUA than in others. Conclusion Based on the results of the study, drama proved to be a valuable and timely intervention strategy that created awareness among university students on the risks of using sharp objects to make marks on the body.
Keywords: drama